Psychosocial interventions with groups of elderly - Rabelo, Dóris Firmino (2013)
Psychosocial interventions with groups are an important tool for the care of the elderly population and on the subject, there is a lack of teaching materials. The purpose of this article is to present suggestions for steps that can guide the group work with the elderly. The suggestions involve the intervention plan: the analysis of the demand, the context of the group and of the place where the activities will be carried out, the skills required to work with the elderly, the choice of the central theme of the proposed intervention, and the meetings structure, from first to last.